Fossil remains of the genus Crataegus (Rosaceae, Amygdaloideae) from south-eastern Armenia - Ivan Gabrielyan; Merine Sargsyan; Arpine Achoyan (Acta Palaeobotanica)
As a result of the research, we determined the sectional affiliation of fossil remains of the genus Crataegus from the Early Pleistocene of the south-eastern part of Armenia, in the middle reaches of the Vorotan River. Plant fossils and imprints help to establish the distribution of species over the Earth’s surface during different geological periods. Of particular interest are the findings of species of the genus Crataegus , which is considered to be systematically very complex due to its inherent hybridization, apomixis, and polyploidy. In the modern flora of Armenia, the genus Crataegus is represented by three sections with 23 species. Comparative macromorphological analysis of fossil and modern hawthorns showed that the studied fossil remains belong to the section Crataegus . Among the species found in the territory, in terms of macromorphological characteristics, they are close to Crataegus rhipidophylla , C. caucasica and C. monogyna .